2011
DOI: 10.1111/j.1478-3231.2011.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Hippo kinase signalling in Human hepatic malignancies

Abstract: Background/Aims: Hepatocellular carcinoma (HCC), cholangiocarcinoma (CC) and hepatoblastoma (HB) are the main hepatic malignancies with limited treatment options and high mortality. Recent studies have implicated Hippo Kinase pathway in cancer development but detailed analysis of Hippo Kinase signaling in human hepatic malignancies, especially CC and HB, is lacking. Methods: We investigated Hippo Kinase signaling in HCC, CC and HB using cells and patient samples. Results: Increased expression of yes-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(118 citation statements)
references
References 26 publications
6
109
0
3
Order By: Relevance
“…Consistent with these findings, the comprehensive survey of the most common solid cancer types revealed elevated YAP protein levels and nuclear localization in multiple human cancers, including HCC, cholangiocarcinoma (CC) and hepatoblastoma (HB) [5,13]. Furthermore, clinical studies showed that YAP was an independent prognostic marker for overall survival and disease-free survival for HCC patients and that it was associated with tumor differentiation [14].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Consistent with these findings, the comprehensive survey of the most common solid cancer types revealed elevated YAP protein levels and nuclear localization in multiple human cancers, including HCC, cholangiocarcinoma (CC) and hepatoblastoma (HB) [5,13]. Furthermore, clinical studies showed that YAP was an independent prognostic marker for overall survival and disease-free survival for HCC patients and that it was associated with tumor differentiation [14].…”
Section: Introductionsupporting
confidence: 56%
“…On the contrary, uninhibited YAP localizes in the nucleus where it serves as a co-activator for the TEAdomain family member (TEAD) group of DNA-binding transcription factors. The YAP/TEAD complex promotes proliferative and survival programs by inducing the expression of target genes [4][5][6]. Notably, both the transgenic overexpression of YAP in mice [3,7] and the liver-specific knockout of Mst1/2 or Sav1 [8][9][10][11] expanded the liver size and ultimately induced HCC, revealing a significant role for the Hippo pathway in regulating organ size and tumorigenesis in mammals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippo, a highly conserved growth control pathway, is deregulated in several human malignancies (5-7) including human CCA (8,9). Recently, we reported that direct transfection of the biliary tree with a constitutively active mediator of the Hippo pathway, YAPS127A, along with mouse myr-Akt as a permissive factor, induces CCA in mice (10).…”
mentioning
confidence: 99%
“…Furthermore, in these studies YAP1 has been implicated as an oncogene which has been altered in different kinds of human digestive system cancers, especially HCC [64]. For instance, a study aimed at evaluating the expression of YAP1 in 115 cases of human HCC samples has identified significant difference in YAP1 protein levels between normal and cancerous tissues [65].…”
Section: Hippo Pathwaymentioning
confidence: 99%